Timing of Puberty and Late Pubertal Height in Saudi Schoolboys: Riyadh Puberty Study II - Ibrahim Al Alwan; Haifa Alfaraidi; Fahad Al Juraibah; Mohamed Al Dubayee; Amir Babiker; Waleed Tamimi; Dania Musalli; Manal Alsheikh; Motasim Badri (International Journal of Endocrinology)
Objective. Puberty has a significant contribution to the final height. Therefore, it is crucial to understand the normal variations in the onset and tempo of puberty in a specific population. In this study, we aimed to provide normative data on the timing of puberty and late pubertal height (LPH) in Saudi schoolboys in Riyadh. Methods. This is a cross-sectional field study (2011–2013) including Saudi schoolboys (grades 1–12; aged 6 to 19 years). Schools were chosen to represent the population from urban and rural areas in the Riyadh region. Pubertal maturity staging for gonads was assessed by measuring testicular size using a Prader orchidometer and assessing the Tanner staging of pubic hair. The marginal mean age was calculated using regression analysis. Results. We recruited 1086 schoolboys. The estimated mean age of pubertal onset at G2 was 11.8 (95% CI 11.60–12.0) years, for gonadal development at G3 was 13.2 (95% CI 12.9–13.5), G4 = 15.0 (95% CI 14.7–15.2), and G5 = 16.1 (95% CI 15.9–16.3) years, and for pubic hair stage 2 (PH2) was 12.6 (95% CI 12.4–12.9) years. The estimated time from G2/PH2 to G5/PH5 was 4.3 and 3.9 years, respectively. At the onset of puberty, the mean height was 144.7 cm and it reached 167.8 cm at G5 with a pubertal height gain of 23.1 cm. Conclusion. Our data present the norms of the timing of puberty and LPH in Saudi schoolboys. Saudi adolescent males are shorter than some European and American comparatives mainly due to shortness during childhood. However, they could have shorter LPH than Turkish, Greek, Thai, and Japanese due to a less pubertal height gain.